Evaluasi Kebijakan Persyaratan dan Penataan Minimarket di Kota Bandar Lampung - Febrihanuddin, Rifky (LPPM Universitas Mataram, 2020)
The growth of minimarkets in Bandar Lampung increases by 20 (twenty) percent every year causing a concern that it will shut down traditional minimarket (warung). Minimarket establishment has been regulated in Mayor Regulation No. 11 Year 2012 concerning Minimarket Terms and Arrangement. However, this policy hasn’t been able to control the growing population of minimarket growths. The type of research was descriptive with a qualitative approach. This study used data collection techniques: interviews, observation and documentation.The results of this research is on technical feasibility aspects, they have achieved the initial purpose, but are too soft towards some violation of regulation which does not satisfy the target group. Furthermore, economic and financial aspects have been well implemented on the manufacturing side but are still weak in enforcement. In political viability aspect, this policy does not violate the previous regulations. However, this policy is not accepted by traditional minimarket (warung), because it pays little attention to the target group. Many minimarket owners do not implement this policy in accordance with what has been determined by government. Furthermore, administrative aspects of the government have implemented and monitored this policy in accordance with applicable regulations and cooperate with other agencies